Dielectric properties of (Al3+，Nb5+) co-doped CaTiSiO5 ceramics at elevated temperature. (September 2019) - Peng, Xiaoxiao; Liu, Zhifu; Gu, Yan; Zhang, Faqiang; Li, Yongxiang
Abstract: The CaTi(1-x) (Al0.5 Nb0.5 )x SiO5 (0 ≤ x ≤ 0.1) ceramics were prepared by the conventional solid-state method. Al and Nb co-doping improved the high temperature stability of the CaTiSiO5 material and no obvious phase transition was found at temperature up to 623 K for x ≥ 0.03. A dielectric constant of 53, dielectric loss of 0.001, resistivity of 8.5 × 10 13  Ω cm, and breakdown strength of 1064.7 kV/cm was obtained for the CaTi0.97 (Al0.5 Nb0.5 )0.03 SiO5 ceramics at room-temperature. The dielectric constant is stable over a wide temperature range and a resistivity of 9.0 × 10 10  Ω cm could still be achieved up to 573 K. The P-E loops measurements showed that energy storage efficiencies of 96% and 88.6% could be obtained at room-temperature and 453 K, respectively, for the CaTi0.97 (Al0.5 Nb0.5 )0.03 SiO5 ceramics. The excellent dielectric properties at elevated temperature indicate that titanite based ceramics stabilized by Al and Nb co-doping could be promising candidates for high temperature ceramic capacitors application. Highlights: The pure high-temperature monoclinic A21 /a phase of doped CaTiSiO5 was obtained. Co-doping of Al 3+ and Nb 5+ ions stabilizes the crystal phase at elevated temperatures up to 623 K. Stable dielectric constant and high resistivity are achieved over a wide temperature range up to 573 K.